Pengaruh Penguasaan Numerik dan Penguasaan Verbal terhadap Prestasi Belajar Matematika - Martua Manullang (Universitas Negeri Malang, 2016)
This study aims at finding out the influence of numeric and verbal abilities on Mathematics achievement of students of State Senior High Schools in Medan. The subjects involved 258 students selected through stratified random sampling. Data was collected by using tests of Mathematics, Numeric, and Verbal mastery developed by the researcher. The result show that the averange scores of numeric, verbal, and mathematics mastery are 14.67, 20.26, and 14.43 respectively.